2019
DOI: 10.1371/journal.pone.0223277
|View full text |Cite
|
Sign up to set email alerts
|

Macrogeographic genetic structure of Lutzomyia longipalpis complex populations using Next Generation Sequencing

Abstract: Lutzomyia longipalpis is the main vector of Leishmania infantum, the causative agent of visceral leishmaniasis in the Neotropical realm. Its taxonomic status has been widely discussed once it encompasses a complex of species. The knowledge about the genetic structure of insect vector populations helps the elucidation of components and interactions of the disease ecoepidemiology. Thus, the objective of this study was to genotypically analyze populations of the Lu. longipalpis complex from a macrogeographic pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…longipalpis in Brazil has been recently explored by Casaril et al, who demonstrated the occurrence of three Lu. longipalpis populations in endemic municipalities [51]. Such processes of divergence and speciation of vectors represent mechanisms generating the heterogeneity of vector capacity and competence, as well as vector susceptibility to infectious agents or insecticides.…”
Section: Inferences On the Transmission Dynamics Of Neotropical L Inmentioning
confidence: 99%
“…longipalpis in Brazil has been recently explored by Casaril et al, who demonstrated the occurrence of three Lu. longipalpis populations in endemic municipalities [51]. Such processes of divergence and speciation of vectors represent mechanisms generating the heterogeneity of vector capacity and competence, as well as vector susceptibility to infectious agents or insecticides.…”
Section: Inferences On the Transmission Dynamics Of Neotropical L Inmentioning
confidence: 99%
“…al., who demonstrated the occurrence of three Lu. longipalpis populations in endemic municipalities [51]. Such processes of divergence and speciation of vectors represent mechanisms generating the heterogeneity of vector capacity and competence, as well as vector susceptibility to infectious agents or insecticides.…”
Section: Inferences On the Transmission Dynamics Of Neotropical L Inmentioning
confidence: 99%
“…However, two main obstacles prevented the generalization of these findings: (a) the genetic polymorphism of the Lu. longipalpis complex, with ongoing cryptic speciation processes and introgression between sibling species, with different vector capacity or spread potential (Casaril et al 2019); and (b) the plasticity that allows Lu. longipalpis dispersion and adaptation to different environments, probably caused by the aforementioned genetic heterogeneity, that consequently made different variables critical in different scenarios with disparate or even contradictory results (Lainson & Rangel 2005).…”
Section: Introductionmentioning
confidence: 99%